1992
DOI: 10.1002/syn.890120310
|View full text |Cite
|
Sign up to set email alerts
|

Fischer and Lewis rat strains differ in basal levels of neurofilament proteins and their regulation by chronic morphine in the mesolimbic dopamine system

Abstract: We studied levels of neurofilament (NF) proteins in the ventral tegmental area (VTA), and other regions of the central nervous system, of two genetically inbred rat strains, Lewis (LEW) and Fischer (F344) rats. These strains represent genetically divergent populations of rats that have been used to study possible genetic factors involved in a variety of biological processes, including drug addiction: compared to F344 rats, LEW rats show a much higher preference for several classes of drugs of abuse. We found 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
90
2
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(100 citation statements)
references
References 51 publications
7
90
2
1
Order By: Relevance
“…The SD rat chosen was also based on our pilot study, in which SD rats showed significant CPP for cocaine at 10 mg/kg, whereas Fischer 344 (F344) rats did not. This is consistent with previous reports by others (Guitart et al, 1992;Kosten et al, 1994;Harris et al, 2005).…”
Section: Introductionsupporting
confidence: 94%
“…The SD rat chosen was also based on our pilot study, in which SD rats showed significant CPP for cocaine at 10 mg/kg, whereas Fischer 344 (F344) rats did not. This is consistent with previous reports by others (Guitart et al, 1992;Kosten et al, 1994;Harris et al, 2005).…”
Section: Introductionsupporting
confidence: 94%
“…11, NO.2 The importance of genetic factors in establishing individual responsiveness to drugs of abuse is indicated by differences in drug-related behaviors among differ· ent inbred animal strains (e.g., Lewis and Fischer rat s). The Lewis rat self-administers opiates, cocaine, and al cohol to a greater extent than the Fischer rat (George and Goldberg 1989), and develops a greater degree of conditioned place preference to cocaine and morphine (Guitart et al 1992;Kosten et al 1994). The Lewis rat also exhibits a greater facilitation in brain self-stimu· lation thresholds in response to cannabinoids than the Fischer rat (Gardner and Lowinson 1991).…”
Section: Contribution Of Intracellular Messenger Proteins To Individumentioning
confidence: 99%
“…Genetic and environmental factors cannot be viewed as separate, independent variables; rather, it is the in teraction between the two that determines an individ ual's predilection for drug addiction. An illustration of such interactions are the fmdings that chronic exposure to drugs of abuse or to glucocorticoids produces diff er ent behavioral effects, and different biochemical adap tations in the mesolimbic dopamine system, in Lewis and Fischer rats (Guitart et al 1992(Guitart et al , 1993Ortiz and Nes tler 1993). In this way, Lewis and Fischer rats provide a novel experimental system to investigate the specifIc genetic and environmental factors that combine to de termine the biochemical phenotype in the mesolimbic dopamine system and the various drug-related be haviors regulated via this neural pathway.…”
Section: Contribution Of Intracellular Messenger Proteins To Individumentioning
confidence: 99%
“…For example, compared to LEW rats, F344 rats are reported to have greater AMPH-induced locomotion at doses between 1 and 2 mg/kg (George et al, 1991;Miserendino et al, 2003; but see Camp et al, 1994, for methamphetamine). LEW rats, in contrast, tend to exhibit greater behavioral sensitization after repeated cocaine or methamphetamine treatment (Camp et al 1994;Kosten et al 1994;Haile et al 2001) and enhanced conditioned place preference for cocaine, nicotine and morphine (Guitart et al 1992;Kosten et al 1994;Horan et al 1997). Furthermore, LEW rats acquire intravenous (i.v.)…”
Section: Introductionmentioning
confidence: 99%